The Relationship between Age, Education, Occupation, and Parity with the First Antenatal Care Visit (Pure K1) Among Pregnant Women in 2025 - Ni Nyoman Suartini; Sri Rahayu; Ni Made Dwi Mahayati (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2026)
The first antenatal care visit (K1) is an essential component of maternal health services aimed at early detection of pregnancy risks and timely intervention, ideally before 12 weeks of gestation. However, many pregnant women still attend their first visit late, increasing risks for both the mother and the fetus. K1 coverage at UPTD Puskesmas Klungkung II decreased to 58.18% in 2024. This study aimed to analyze the relationship between maternal age, education, occupation, and parity with the timeliness of K1 visits. A quantitative cross-sectional study was conducted from April to May 2025, involving 82 first-trimester pregnant women selected via total sampling. Data were analyzed using the Chi-Square test. The results showed that 82.9% of respondents made timely K1 visits. However, there was no significant relationship between age, education, occupation, or parity and the timeliness of K1 (p > 0.05). Although higher proportions of timely K1 visits were found among women aged 20–35 years (87.8%), those with secondary education (73.2%), unemployed women (72%), and parity ≤3 (80.5%), these differences were not statistically significant. Demographic factors were not the primary determinants of K1 attendance. Efforts should focus on health education, service accessibility, and family support to improve timely antenatal care utilization.